2019
DOI: 10.1089/ther.2018.0023
|View full text |Cite
|
Sign up to set email alerts
|

Intra-Arrest Induction of Hypothermia via Large-Volume Ice-Cold Saline for Sudden Cardiac Arrest: The New York City Project Hypothermia Experience

Abstract: Therapeutic hypothermia, the standard for post-resuscitation care of out-of-hospital sudden cardiac arrest (SCA), is an area that the most recent resuscitation guidelines note ''has not been studied adequately.'' We conducted a two-phase study examining the role of intra-arrest hypothermia for out-of-hospital SCA, first standardizing the resuscitation and transport of patients to resuscitation centers where post-resuscitation hypothermia was required and then initiating hypothermia during out-of-hospital resus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 39 publications
(30 reference statements)
0
17
0
Order By: Relevance
“…After the rst screening procedure, 43 studies were assessed for eligibility. Of those, 35 did not t inclusion criteria, as reported in Figure 1; a total of 8 studies [9][10][11][12][13][14][15][16], including 3493 patients, were then included for meta-analysis.…”
Section: Study Selectionmentioning
confidence: 99%
See 4 more Smart Citations
“…After the rst screening procedure, 43 studies were assessed for eligibility. Of those, 35 did not t inclusion criteria, as reported in Figure 1; a total of 8 studies [9][10][11][12][13][14][15][16], including 3493 patients, were then included for meta-analysis.…”
Section: Study Selectionmentioning
confidence: 99%
“…The characteristics of the selected studies are summarized in Table 1. We identi ed 4 RCTs (high quality of evidence for two [12,16] and moderate for two [10,14]), two prospective studies (low level of evidence in one [9] and very low quality of evidence [15] in the other, which compared a prospective cohort with historical controls) and two retrospective studies (very low quality of evidence [11,13]). The ROB for RCTs was low in three studies [10,12,16] and showed some concerns in one [14] ( Table 2).…”
Section: Study Characteristicsmentioning
confidence: 99%
See 3 more Smart Citations